THU0395 Tumour necrosis factor-alpha as a master regulator of inflammation in erdheim-chester disease: Rationale for the successful treatment of two patients with infliximab. (23rd January 2014) - Dagna, L.; Corti, A.; Langheim, S.; Guglielmi, B.; Cavalli, G.; De Cobelli, F.; Doglioni, C.; Fragasso, G.; Sabbadini, M.G.; Ferrarini, M.
Abstract : Background: Erdheim-Chester disease (ECD) is a rare form of systemic non-Langerhans histiocytoses of unknown aetiology. IFN-α is the first-line therapy, but its efficacy varies according to sites of disease involvement. When the cardiovascular or central nervous systems are involved, IFN-α treatment is scarcely effective and the prognosis is extremely poor. Evidence is accumulating that inflammatory cytokines and chemokines are responsible for histiocyte recruitment and accumulation inside ECD lesions. Objectives: We evaluated the levels of TNF-α, interleukin (IL)-1b, IL-6, CCL2, CCL4, CCL5, CXCL8, CXCL10, and of the TNF-α soluble receptor-I and -II (which are bona fide markers of TNF-α activation) in ten patients with ECD and in healthy controls. We then treated two patients with cardiovascular ECD who were ineligible or unresponsive to IFN-α treatment with the anti-TNF-α neutralizing antibody infliximab, with a follow-up of 28 and 10 months, respectively. Methods: Plasma levels of cytokines and chemokines were determined by Bio-Plex Multiple Cytokine Assay. sTNF-RI and sTNF-RII levels were assessed byELISA. Two independent sample permutation tests were performed to compare data obtained from ECD patients and controls. Unilateral alternatives were specified and examined. The significance level was chosen to be 0.05. Logistic regression was used to predict the group membership of a new case-patient. Results: Patients with ECD had significantly increased plasma levels of TNF-α, soluble TNF-receptors, and TNF-regulated factors (IL-1b, IL-6, CCL2, and CCL5), as compared to healthy individuals. During follow-up, both treated patients showed a progressive reduction in the levels of circulating pathogenic cyto-chemokines and sTNF-Rs as well as improvement of symptoms, cardiac involvement and function. The treatment wasn't associated to any significant side effect. Conclusions: Overall our data indicate that TNF-α may have a key role in the pathogenesis of ECD and that TNF-α targeting could represent an effective therapeutic strategy for the disease. References: Haroche J et al. Variability in the efficacy of interferon-alpha in Erdheim-Chester disease by patient and site of involvement: results in eight patients. Arthritis and rheumatism 2006 Haroche J et al. Cardiovascular involvement, an overlooked feature of Erdheim-Chester disease: report of 6 new cases and a literature review. Medicine 2004 Stoppacciaro A et al. Immunohistochemical evidence of a cytokine and chemokine network in three patients with Erdheim-Chester disease: implications for pathogenesis. Arthritis and rheumatism 2006 Dagna L et al. Erdheim-Chester disease: report on a case and new insights on its immunopathogenesis. Rheumatology 2010 Arnaud L et al. Systemic perturbation of cytokine and chemokine networks in Erdheim-Chester disease: a single-center series of 37 patients. Blood 2011 Disclosure of Interest: None Declared